Evaluation of the Ages and Stages Questionnaires in identifying children with neurosensory disability in the Magpie Trial follow-up study. - Yu, L; Hey, E; Doyle, L; Farrell, B; Spark, P; Altman, D; Duley, L (2007)
AIM: To evaluate performance of the Ages and Stages Questionnaires (full ASQ), and a shortened version (short ASQ), in detecting children with severe neurosensory disability in the Magpie Trial follow-up study. METHODS: All children, born to women in the Magpie Trial and selected for follow-up, with a completed full 30 items and/or short 9-items ASQ were included in this analysis. Sensitivity and specificity, corrected for verification bias, were computed to assess detection ability. RESULTS: Of the 2046 children who completed a full ASQ, 406 (19.8%) failed the assessment, 54 of whom had confirmed neurosensory disability. Adjusted sensitivity and specificity (95% confidence intervals) were 87.4% (62.9-96.6%), and 82.3% (80.5-83.9%), respectively. Two of the five domains in the full ASQ (Fine Motor and Problem Solving) contributed little to detection ability. Sensitivity and specificity for the short ASQ were 69.2% and 95.7%, respectively. CONCLUSIONS: Sensitivity of the full ASQ for severe neurosensory disability is generally good, and does not appear to be much reduced by restricting questions to three out of the five domains. The short ASQ reported here reduced performance, although this might be improved by a different choice of questions or scoring system.